2022
DOI: 10.1111/dmcn.15404
|View full text |Cite
|
Sign up to set email alerts
|

Chronic pain, psychological distress, and quality of life in males with Duchenne muscular dystrophy

Abstract: Aim: To describe chronic pain in Duchenne muscular dystrophy (DMD) from children's/adolescents' perspectives, explore patient variables associated with selfreported pain, and examine the relationship between chronic pain, psychological functioning, and health-related quality of life (HRQoL).Method: This observational study included a paediatric cohort (aged 8-18 years; median age 9 years 4 months) with DMD under multidisciplinary care (n = 45). Clinical data of the latest visit were extracted from the electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 44 publications
(112 reference statements)
0
5
0
Order By: Relevance
“…Compared to these two well-validated comprehensive scales, the CFSD and EK scales, the DMDSAT lacks items assessing other aspects of DMD, especially dysphagia and pain. Since dysphagia and pain are symptoms that require careful attention and are strongly associated with quality of life [ 23 ], extending to DMDSAT questionnaires on swallowing function and pain would provide more information and help plan the most appropriate intervention. Although DMDSAT is a scoring system, its purpose is to document functional status rather than to provide a quantitative evaluation of physical function.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to these two well-validated comprehensive scales, the CFSD and EK scales, the DMDSAT lacks items assessing other aspects of DMD, especially dysphagia and pain. Since dysphagia and pain are symptoms that require careful attention and are strongly associated with quality of life [ 23 ], extending to DMDSAT questionnaires on swallowing function and pain would provide more information and help plan the most appropriate intervention. Although DMDSAT is a scoring system, its purpose is to document functional status rather than to provide a quantitative evaluation of physical function.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the lack of precise demographic data and the small sample size limit the generalizability of these findings. However, pediatric neuromuscular disorders are rare, and a small sample size is not unusual for this population [17][18][19][20][21][22][23][24]. Other limitations include possible selection bias, in particular sampling and volunteer bias subtypes.…”
Section: The Overall Psychosocial Impact Of Covid-19 On Children and ...mentioning
confidence: 99%
“…It is interesting to see research carried out in order to understand the role and perception of pain and management (such as cough assistance) for individuals like me. 1,2 Personally, I cannot say that pain specifically or the use of cough assist have affected my QoL as a whole. The factor that has contributed most meaningfully has been participation in family life.…”
mentioning
confidence: 99%
“…Additionally, I have a number of positional aids that are essential for my comfort. I was not surprised to see that no participants in the pain study by Huang et al reported taking analgesics, 1 as they do not help me effectively. Consequently, the fear of experiencing pain is sometimes greater than the pain itself, so I avoid getting into certain situations.…”
mentioning
confidence: 99%
See 1 more Smart Citation